2014
DOI: 10.1074/jbc.m113.544049
|View full text |Cite
|
Sign up to set email alerts
|

Residue Histidine 50 Plays a Key Role in Protecting α-Synuclein from Aggregation at Physiological pH

Abstract: Background: Mutations of ␣-synuclein (␣Syn) can cause early-onset familial Parkinson disease (PD). Results: The H50Q, H50D, or H50A substitution promotes, whereas the H50R substitution inhibits, ␣Syn aggregation in vitro. Conclusion:The recently identified PD-causing ␣Syn mutant, ␣Syn(H50Q), accelerates ␣Syn aggregation. Significance: The partial positive charge of His-50 at physiological pH likely plays a role in suppressing ␣Syn aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
4
22
1
Order By: Relevance
“…To investigate further the causes of the increased aggregation propensity of the H50Q variant, we characterize the monomeric ensembles of both WT and H50Q α-Syn using NMR spectroscopy. In previous reports, comparative spectroscopic analyses have revealed broadly similar structural ensembles in the WT and H50Q variants, with a small number of chemical shift changes around the site of the mutation ( 18 20 ) and, in some cases, additional perturbations in the C-terminal region ( 18 , 19 ). Here we carry out a comprehensive chemical shift-based analysis of WT and H50Q α-Syn, using the δ2D algorithm ( 24 ) to scrutinize changes in the residual secondary structure of the variant.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…To investigate further the causes of the increased aggregation propensity of the H50Q variant, we characterize the monomeric ensembles of both WT and H50Q α-Syn using NMR spectroscopy. In previous reports, comparative spectroscopic analyses have revealed broadly similar structural ensembles in the WT and H50Q variants, with a small number of chemical shift changes around the site of the mutation ( 18 20 ) and, in some cases, additional perturbations in the C-terminal region ( 18 , 19 ). Here we carry out a comprehensive chemical shift-based analysis of WT and H50Q α-Syn, using the δ2D algorithm ( 24 ) to scrutinize changes in the residual secondary structure of the variant.…”
Section: Introductionmentioning
confidence: 85%
“…The recently identified H50Q α-Syn mutation ( 16 , 17 ) was shown to aggregate faster in vitro compared with the WT counterpart ( 18 21 ). Here we compare sequence-based predictions of aggregation propensity ( 22 , 23 ) with further experimental observations of aggregation behavior in the WT and H50Q α-Syn.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, however, interactions between ␣-synuclein and CsgC were found to prevent amyloid polymerization (6). The authors suggested that interactions between CsgC and ␣-synuclein enhanced intraprotein interactions, shielding NAC from exposure and thus preventing fibrillization of ␣-synuclein (135). Furthermore, Westermark and colleges showed that curli fibers enhance the fibrillization of amyloid protein A, which is implicated in the pathogenesis of systemic amyloidosis (136).…”
Section: Enteric Biofilm Amyloids and Neurodegenerative Diseasesmentioning
confidence: 99%
“…[1][2][3][4][5] In PD these intraneuronal proteinaceous inclusion bodies, referred to as Lewy bodies, are composed primarily of fibrillar and aggregated forms of wild-type and post-translationally modified a-synuclein. 1,2,6 Various mutations in the gene coding for a-synuclein (including A30P, 7 H50Q, 8,9 G51D, 10 A53T, 11 and E46K 12 ) are associated with familial forms of the disorder, although they account for only 1-5% of PD cases. 13 Understanding the role of the molecular and structural determinants of the functional and aggregation properties of a-synuclein is therefore pivotal in elucidating the role of this protein in the pathogenesis of PD, as well as identifying novel diagnostic and therapeutic strategies for the treatment of the wider family of synucleinopathies.…”
Section: Introductionmentioning
confidence: 99%